Rare Case of Placental Mesenchymal Dysplasia - Sripriya Thiruvengadathan; Vidya Chaya; Venkateswaralu Venkateswaralu (International Journal of Medical Research and Review, 2015)
Placental mesenchymal dysplasia is a rare benign condition complicating pregnancy. Fetus usually appears normal, with no significant abnormality. However association with Beckwith Wideman syndrome has been reported. Placenta often shows cystic areas in ultrasound and has to be differentiated from molar pregnancy. Placental villous chorangiosis is the hallmark of placental mesenchymal dysplasia.